Effect of welding nugget diameter on the tensile strength of the resistance spot welding joints of same sheets metal - Walter, Jenis (2009)
Resistance spot welding is commonly used in the automotive industry, because it has the advantage which is high speed, high-production assembly lines and suitability for automation. The welded joints are exposed to the variables of load and pressure, these conditions made the welded joint to rupture. The objective of this project is to study the effect of welding nugget diameter on the tensile strength of the resistance spot welded joints. Using the tensile test method to analyze the selected size of the nugget diameter to determine the maximum load that can be applied before the specimen is rupture or tears apart. The selected materials are Aluminum and Mild steel sheets metal.